2015
DOI: 10.1155/2015/710363
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Autoimmunity in the Context of Type 2 Diabetes Mellitus: Implications for Vitamin D

Abstract: Vitamin D deficiency has been associated with both type 2 diabetes mellitus (T2DM) and autoimmune disorders. The association of vitamin D with T2DM and thyroid autoimmunity (TAI) has not been investigated. Thus, we aimed to explore the putative association between T2DM and thyroid autoimmunity (TAI) focusing on the role of 25-hydroxy-vitamin D (25(OH)D). Study population included 264 T2DM patients and 234 controls. To explore the potential association between 25(OH)D and thyroid autoimmunity while controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
2
15
0
3
Order By: Relevance
“…Our study has shown a higher prevalence of thyroid autoimmunity in Ghanaian T2DM subjects compared to controls with one in five T2DM subjects testing positive for thyroid autoimmunity compared to one in twenty seen among the controls. This finding is consistent with those of Akbar [4], Yasmin [25] and Konstantinos [26] who recorded significantly higher prevalence of thyroid autoimmunity in T2DM subjects compared to controls, with prevalence ranging between 10% and 43% among T2DM subjects. On the contrary, Cardoso et al [4] and Afkhami-Ardekani et al [22] recorded no significant difference between the 2 groups.…”
Section: Discussionsupporting
confidence: 93%
“…Our study has shown a higher prevalence of thyroid autoimmunity in Ghanaian T2DM subjects compared to controls with one in five T2DM subjects testing positive for thyroid autoimmunity compared to one in twenty seen among the controls. This finding is consistent with those of Akbar [4], Yasmin [25] and Konstantinos [26] who recorded significantly higher prevalence of thyroid autoimmunity in T2DM subjects compared to controls, with prevalence ranging between 10% and 43% among T2DM subjects. On the contrary, Cardoso et al [4] and Afkhami-Ardekani et al [22] recorded no significant difference between the 2 groups.…”
Section: Discussionsupporting
confidence: 93%
“…In an elderly population with a high prevalence of vitamin D deficiency/insufficiency patients with type 2 diabetes were found to be 2.5 times more likely to have AITD compared to a nondiabetic individuals, but, interestingly, the higher the serum 25(OH)D 3 levels were, the higher this chance was (49). In women with polycystic ovary syndrome (PCOS), 25(OH)D 3 levels were significantly lower in subjects with AITD than in those without AITD (p = 0.02).…”
Section: Human Studiesmentioning
confidence: 96%
“…The evidence is increasingly pointing towards vitamin D significant role in reducing the incidence of autoimmune diseases [1]. Over recent, numerous non-skeletal diseases associated with vitamin D deficiency have been reported including hypothyroidism [2].…”
Section: Introductionmentioning
confidence: 99%